Efeito da servitização no desempenho de pequenas e médias empresas fabricantes de bens de capital - Queiroz, Stefânia Aparecida Belute (Universidade Federal de São Carlos, 2018)
Servitization is as an emergent competitive strategy for manufacturing companies. One research gap concerns the need to better understand its impact on firms’ performance. Prior empirical studies have provided inconsistent results regarding servitization-performance relationship. Moreover, the existing literature has concentrated on servitization in large-sized companies. This article aims to examine the factors influencing the servitization strategy in small and medium enterprises (SMEs) and the impact of this strategy on SME´s performance. The study uses data from 176 Brazilian SMEs and applies structural equation modeling technique to test a set of research hypotheses. The outcomes provide support for the hypothesized positive relationship between servitization strategy and performance by showing that servitization contributes to increase the financial and non-financial performance for SMEs regardless their level of servitization or proportion of service income. Moreover, external factors directly influence the servitization strategy in SMEs and indirectly affect SMEs´ performance through servitization strategy. This work also discusses theoretical and managerial implications.
Keywords: Servitização; Pequena e média empresa; PMEs; Desempenho financeiro; Desempenho não-financeiro; Empresas de manufatura; Servitization; Small and medium enterprice; Financial performance; Non-financial performance; Manufacturing companies; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO